Sejarah Pimpinan Cabang Muhammadiyah Cakru di Desa Cakru Kecamatan Kencong Kabupaten Jember Pada Tahun 1976-2000 - Muhammad Sandy Wijaya (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study examines the historical development of Pimpinan Cabang Muhammadiyah (PCM) Cakru in Cakru Village, Kencong District, Jember Regency, from 1976 to 2000. The research addresses three main questions: the background of PCM Cakru's establishment in 1976, its organizational development during 1976-2000, and its impact on the Cakru Village community during this period. The research employs historical methodology consisting of five stages: topic selection, heuristics (source collection), verification (source criticism), interpretation, and historiography. Primary sources include official documents, organizational archives, land ownership records, and interviews with key figures, while secondary sources comprise books, theses, and relevant academic articles. The theoretical framework utilizes Talcott Parsons' structural-functionalism theory with the AGIL scheme (Adaptation, Goal Attainment, Integration, Latency) and organizational sociology approach. Findings reveal that PCM Cakru originated from a small religious study group in 1927, which evolved into a formal Muhammadiyah organization in 1941 and was officially recognized as a branch in 1976 through Decree No. M/021/76. The organization demonstrated significant development through membership growth, asset expansion (acquiring 15 land parcels totaling 65,359 square meters through waqf), and establishment of various charitable institutions. PCM Cakru's educational contributions included founding five Madrasah Ibtidaiyah (1937-1964), one junior high school (1954), and notably the Sekolah Pertanian Menengah Atas (SPMA) Muhammadiyah Cakru in 1977 the first and only agricultural vocational school in Jember at that time. The organization's impact on society manifested in three dimensions: educational advancement through establishing accessible Islamic-based schools, social welfare through constructing eight mosques and 30 prayer facilities by 1998, and agricultural modernization through SPMA which produced skilled agricultural professionals. Despite challenges including internal conflicts, regeneration issues, and declining student enrollment in certain institutions, PCM Cakru maintained its existence and continued contributing to community development, demonstrating the successful application of Muhammadiyah's dakwah approach in rural contexts.
FINALISASI oleh Arif 2026 Mei 26
Keywords: Muhammadiyah; Organizational History; Islamic Education; Rural Development; Cakru; Kencong; Jember